Digital terrestrial television in Nigeria: A technical review of path loss modeling and optimization techniques - Abolaji Okikiade Ilori; Kamoli Akinwale Amusa; Tolulope Christianah Erinosho (International Journal of Advances in Applied Sciences, 2022)
The switch from analog to digital terrestrial broadcasting (DTTV) has resulted in a substantial shift in the contemporary television broadcasting environment, introducing a new means of transmitting content, as well as a new and upgraded process that will improve consumer satisfaction by ensuring greater reception. Despite the deadline, only a small percentage of terrestrial television stations in Nigeria have been digitalized. This work takes a critical review of various aspects of DTTV implementation, ranging from evolution to path loss estimation, prospects and challenges associated with the switch-over on the very high frequency (VHF) communication links as well as various optimization techniques that are adopted for DTTV in Nigeria and sub-Sahara Africa. Findings show that the prospects are bright and numerous benefits are accruable if the government of Nigeria can solve the problems facing its full migration. Furthermore, investigations into the path-loss of DTTV in the ultra-high frequency (UHF) communication links have enjoyed scanty attention, therefore, careful examination and suitable path-loss model development in this frequency regime for television (TV) services across various ecological and vegetation zones should be considered as it will aid the full deployment of DTTV in Nigeria.